Morphological and molecular identification of the cat flea Ctenocephalides felis from Bangladesh. - Md Shamsudduha; Md Mahfuzur Rahman; Jannatun Naher; Azizul Islam Barkat; Sumaiya Akter; Mohammad Shamimul Alam. (Journal of Advanced Veterinary and Animal Research)
Objective: The present study was designed to conduct molecular and morphological identification of cat fleas (Ctenocephalides felis) from Bangladesh along with nucleotide polymorphism and phylogenetic analysis. Materials and Methods: Samples were collected from two hosts (cat and human). The species was identified through morphological studies first, and then DNA was extracted for subsequent molecular analysis. A part of the mitochondrial 16S rRNA gene was amplified by polymerase chain reaction using extracted DNA as a template. The amplified region was sequenced using the Sanger dideoxy method. The sequence was subjected to NCBI BLASTn search. BioEdit and MEGA 11 software were used for multiple sequence alignment (MSA) and generating a phylogenetic tree. Results: Morphological features such as shape, size, and appendages showed similarity with C. felis. The metatibial formula of chaetotaxy (2-2-2-2-1-3) was confirmed for species-level identification. NCBI BLASTn search showed the highest sequence identity with the available sequence of C. felis such as 99.78% (NC_049858.1) and 99.12% (MW420044.1 and MK941844.1) with 100% query coverage. MSA of C. felis sequences from different geographical distributions show their sequence affinities with each other, and the phylogenetic tree presents their relationship with each other. Conclusion: Both morphological and molecular studies clearly indicate the identity and confirmation of cat flea (C. felis) from Bangladesh. [J Adv Vet Anim Res 2025; 12(1.000): 280-286]